Recovery after spinal cord injury is enhanced by anti-Nogo-A antibody therapy — from animal models to clinical trials. Issue 14 (April 2020) - Sartori, Andrea M; Hofer, Anna-Sophie; Schwab, Martin E
Abstract : The ability of the central nervous system to regenerate over long distances after a lesion is restricted by the presence of physical and biochemical barriers, neuronal growth programs changes, and a non-permissive tissue environment. The myelin-derived membrane protein Nogo-A exerts repulsive and neurite growth-inhibitory functions that can critically affect the axonal regeneration capability. Suppression of Nogo-A signaling via function-blocking antibodies, receptor-bodies or genetic manipulation showed a relevant increase in the functional recovery including locomotion and lower urinary tract function in spinal cord injured rodents as well as hand function in monkeys. The currently on-going phase II clinical trials will elucidate the potential relevance of Nogo-A suppression for a novel therapeutic management of spinal cord injury in human patients.